2022
DOI: 10.1177/02841851221087376
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of O-RADS combined with serum CA125 and HE4 for the diagnosis of ovarian tumours

Abstract: Background Ovarian tumors (OTs) are common gynecological tumors in women. It is very important to correctly distinguish benign and malignant OTs. Purpose To assess the diagnostic performance of the American College of Radiology (ACR) Ovarian-Adnexal Reporting and Data System (O-RADS) and evaluate the clinical value of O-RADS combined with serum carbohydrate antigen 125 (CA125) and human epididymis protein 4 (HE4) in differentiating benign from malignant OTs. Material and Methods A retrospective analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Use of the O-RADS lexicon to stratify patients into O-RADS risk groups has been validated retrospectively in 13 other studies [11][12][13][14][15][16][17][18][19][20][21][22]24 and prospectively in 1 study 23 (search strategy and study details shown in the eAppendix and eTable 8 in the Supplement). The prospective study was small (50 patients) and included only tumors in O-RADS 3 to 5.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Use of the O-RADS lexicon to stratify patients into O-RADS risk groups has been validated retrospectively in 13 other studies [11][12][13][14][15][16][17][18][19][20][21][22]24 and prospectively in 1 study 23 (search strategy and study details shown in the eAppendix and eTable 8 in the Supplement). The prospective study was small (50 patients) and included only tumors in O-RADS 3 to 5.…”
Section: Discussionmentioning
confidence: 99%
“…images with or without supplementary review of ultrasonographic reports. In 9 retrospective studies, the reference standard was histology, [12][13][14][15][17][18][19][20]22 in 3 it was histology or results of follow-up, 11,16,24 and in 1 it was the agreed diagnosis of 2 radiologists according to the ultrasonographic images. 21 The reported observed malignancy rates per O-RADS group and the sensitivities and specificities when O-RADS 4 to 5 was used (≥10% malignancy risk) to indicate malignancy are variable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hack [33] proved that adding the information of acoustic shadowing as a benign nding can improve the diagnostic performance of O-RADS. Two recent studies have also focused on combing O-RADS and CA125 [34,35] . They used a combination of statistical methods, whereas this research offered a simpler as well as more practical method to combine CA125 and the O-RADS 4 category, and all got gratifying results.…”
Section: Discussionmentioning
confidence: 99%